Cavernous sinus thrombosis due to ipsilateral sphenoid sinusitis. Issue 1 (29th January 2019) - Dolapsakis, Christodoulos; Kranidioti, Eleftheria; Katsila, Sofia; Samarkos, Michael
Abstract : We report a case of septic thrombosis of the right cavernous sinus in a diabetic woman in her late 70's due to ipsilateral sphenoid sinusitis. The diagnosis was delayed and made only after the abrupt and dramatic appearance of the manifestations of sinus thrombosis. The patient developed, among the other symptoms, right peripheral facial palsy, which is a very rare manifestation in cavernous sinus thrombosis (CST). She was treated with broad-spectrum antibiotics and enoxaparin. The day of the scheduled drainage of sphenoid sinus—24 hours after the initiation of anticoagulation—she developed fatal subarachnoid haemorrhage. Our case demonstrates the difficulty of timely diagnosis of acute sphenoid sinusitis which has emerged as the most common primary infectious source potentially leading in CST. It also underscores the uncertainty concerning the use of anticoagulation in cerebral sinus thrombosis of infectious origin.